Glycosylation of autoantibodies: Insights into the mechanisms of immune thrombocytopenia - Bakchoul, Tamam; Walek, Kathrin; Krautwurst, Annika; Rummel, Mathias; Bein, Gregor; Santoso, Sentot; Sachs, Ulrich J. (Thrombosis and Haemostasis, 2013)
Immune thrombocytopenia (ITP) is a bleeding disorder caused by IgG autoantibodies (AAbs) directed against platelets (PLTs). IgG effector functions depend on their Fc-constant region which undergoes post-translational glycosylation. We investigated the role of Asn279-linked N-glycan of AAbs in vitro and in vivo. AAbs were purified from ITP patients (n=15) and N-glycans were enzymatically cleaved by endoglycosidase F. The effects of native AAbs and deglycosylated AAbs were compared in vitro on enhancement of phagocytosis of platelets by monocytes and complement fixation and activation applying flow cytometry, laser scanning microscopy, and a complement consumption assay. AAb-induced platelet phagocytosis was inhibited by N-glycan cleavage (median phagocytic activity: 8% vs 0.8%, p=0.004). Seven out of 15 native AAbs bound C1q and activated complement. N-glycan cleavage significantly reduced both effects. In vivo survival of human PLTs was assessed after co-transfusion with native or N-glycan cleaved AAbs in a NOD/SCID mouse model. Injection of AAbs resulted in rapid clearance of human platelets compared to control (platelet clearance after 5h (CL5h) 75% vs 30%, p<0.001). AAbs that were able to activate complement induced more pronounced platelet clearance in the presence of complement compared to the clearance in the absence of complement (CL5h 82% vs 62%, p=0.003). AAbs lost their ability to destroy platelets in vivo after deglycosylation (CL5h 42%, p<0.001). N-glycosylation of human ITP AAbs appears to be required for platelet phagocytosis and complement activation, reducing platelet survival in vivo. Posttranslational modification of AAbs may constitute an important determinant for the clinical manifestation of ITP.
Keywords: Thrombocytopenia; autoantibody; ITP; animal model; complement